Factors Affecting on Young Female Entrepreneurial Intention: A Study of Surkhet District - Tiwari, Kamala Kumari (Journal of Nepalese Management and Research, 2025)
This study aims to identify and analyze the factors influencing the entrepreneurial intention of young women in Birendranagar Municipality, Surkhet. Specifically, it examines the impact of economic factors, social and cultural factors, security, and motivation on their willingness to engage in entrepreneurship. A quantitative research approach was employed, utilizing a structured questionnaire to collect data from 305 young female respondents in Birendranagar. Descriptive and inferential analyses were conducted using SPSS 26 and SmartPLS. Regression analysis was applied to assess the relationship between the independent variables (economic factors, social and cultural factors, security, and motivation) and the dependent variable (entrepreneurial intention). The results indicate that economic factors, particularly financial accessibility and economic support, significantly influence entrepreneurial intention. Social and cultural norms also play a crucial role, either encouraging or discouraging women from pursuing entrepreneurship. Personal motivation was found to be a strong driver of entrepreneurial intention. Young women’s entrepreneurial intentions are influenced by a combination of economic factors, social and cultural norms, perceived security, and personal motivation. Access to financial resources, market opportunities, and economic stability can either enable or hinder their entrepreneurial aspirations. Family and societal support, as well as positive cultural attitudes toward entrepreneurship, play a significant role in shaping their willingness to start a business. Additionally, intrinsic and extrinsic motivation such as the desire for financial independence and professional growth are key drivers in their decision to establish and sustain entrepreneurial ventures.